2017
DOI: 10.1007/s10529-017-2503-2
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene biotransformation by Colletotrichum species

Abstract: This is the first report on the biotransformation of these terpenes by Colletotrichum spp. and the biotransformation of limonene to limonene-1,2-diol possibly involves enzymes similar to those found in Grosmannia clavigera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Remarkably, the antifungal activity of these essential oils and their main volatiles was less effective than that of L. virginicum and phenylacetonitrile. Other studies revealed that isolates of Colletotrichum acutatum are able to transform limonene and linalool into limonene‐1,2‐diol, and linalool oxides, respectively [17] . This data and the MIC obtained in this work for both monoterpenes, suggest that C. acutatum is resistant to limonene and linalool.…”
Section: Resultssupporting
confidence: 75%
“…Remarkably, the antifungal activity of these essential oils and their main volatiles was less effective than that of L. virginicum and phenylacetonitrile. Other studies revealed that isolates of Colletotrichum acutatum are able to transform limonene and linalool into limonene‐1,2‐diol, and linalool oxides, respectively [17] . This data and the MIC obtained in this work for both monoterpenes, suggest that C. acutatum is resistant to limonene and linalool.…”
Section: Resultssupporting
confidence: 75%
“…On the other hand, a similar pro le was observed when (S)-(-)-limonene was applied as substrate and C. acutatum and C. nymphaeae were used as biocatalysts. Higher amounts of limonene-1,2-diol were produced (3.08 g/L -1 and 0.06 g/L -1 , respectively), which were accumulated after 192 h (Sales et al 2018b).…”
Section: Fungal Biotransformation Of Limonene For the Production Of Aroma Compoundsmentioning
confidence: 96%
“…Limonene-1,2-diol has been associated with a signi cant inhibitory effect on the pro-in ammatory activities of CD4 + and CD8 + T lymphocytes; a potential anticancer activity. It also has insect-attractant properties besides being used as avoring for beverages, chewing gum, gelatins, and puddings (Molina et al 2015b;Sales et al 2018b;Sales 2019c).…”
Section: Fungal Biotransformation Of Limonene For the Production Of Aroma Compoundsmentioning
confidence: 99%
“…Limonene isomers are the most abundant monoterpene hydrocarbons found in nature. (+)-(R)-limonene is the major constituent of the essential oil obtained from citrus peels [83]. A 50-year literature review shows that the biotransformation of limonene by different types of microorganisms (bacteria, filamentous fungi, and yeasts) produces carveol, carvone, perillyl alcohol, isopiperitenol, α-terpineol, and limonene 1,2-diol [83][84][85] as main components.…”
Section: Terpenesmentioning
confidence: 99%
“…(+)-(R)-limonene is the major constituent of the essential oil obtained from citrus peels [83]. A 50-year literature review shows that the biotransformation of limonene by different types of microorganisms (bacteria, filamentous fungi, and yeasts) produces carveol, carvone, perillyl alcohol, isopiperitenol, α-terpineol, and limonene 1,2-diol [83][84][85] as main components. The biotransformation products of limonene generated by bacteria are mainly perillaldehyde, perillic acid, limonene-1,2-epoxide, and limonene-8,9-epoxide, while isopiperitenone, limonene-4-ol, and cis/trans-mentha-2,8-dienol are commonly generated by filamentous fungi and yeasts.…”
Section: Terpenesmentioning
confidence: 99%